THE INFLUENCE OF PRAGMATICS FAILURE IN CROSS-CULTURAL COMMUNICATION ON UNDERGRADUATE EFL STUDENTS - Ruswandi, Riki; Zahra, Anastacia Fauzia Fazriatu; Wafiroh, Giska Hibbatin (English Review: Journal of English Education, 2025)
This study aims to analyze pragmatic failures in cross-cultural communication. In communication, language is used, language is the most effective instrument that humans have to convey thoughts, ideas, and emotions, or even develop language or cultural differences during conversations. Students majoring in English need to improve their pragmatic competence to communicate effectively with foreign speakers. However, in contrast to pragmatic competence, there is a possibility of misunderstandings involving the target language and the native language, the most common of which is the failure of pragmatics in cross-cultural communication. In this study, the method used is quantitative, using a survey design with descriptive analysis and distributing questionnaires to students at UIN Sunan Gunung Djati. The results found from this study are pragmatic failures in terms of cultural differences, negative language transfer, and also pragmatic competence. In addition, pragmatic failure has a significant impact on the effectiveness of intercultural communication in undergraduate EFL students.